Development of an energy-efficient hybrid electric vehicle air-conditioning system test rig coupled with nanolubricant - Muriban, Jackly; Rizalman, Mamat; Prayogo, Galang Sandy; Mohd Faizal, Jamlos (Faculty Mechanical Engineering, UMP, 2025)
The development of an energy-efficient electric automotive air conditioning system is crucial in addressing the growing concerns over energy consumption and environmental impact in the transportation sector. Prior to assessing the impact of nanolubricants on energy consumption and performance enhancement, a hybrid electric vehicle air conditioning system test rig was developed. Hence, this study focuses on the research and development of an innovative air-conditioning system that incorporates nanolubricants to improve efficiency, thereby reducing overall energy consumption and emissions. The AI2O3/POE nanolubricant was synthesized using a two-step method with a volume concentration of 0.15%. The performance of the hybrid electric vehicle air-conditioning system was evaluated based on its cooling capacity and power consumption. The results indicated that compressor work and power consumption were reduced by up to 21.23% and 36.36%, respectively. Based on these findings, a 0.15 vol.% AI2O3/POE nanolubricant, combined with a 350 g initial refrigerant charge, was determined to be optimal for performance enhancement and power consumption reduction. The findings of this study have provided significant insights into the potential of nanolubricants to enhance the performance of electrically driven compressor (EDC) air-conditioning systems in hybrid and electric vehicles while reducing energy consumption at various operating speeds.